ESENSI SISTEM PENGENDALIAN MANAJEMEN PADA OLAHRAGA CALISTHENICS - Reynaldo Arbaham Setiawan (CALYPTRA, 2018)
This study aims to reveal the Essence of Management Control Systems in Calisthenics Sports where with the concept of Management Control Systems On Sport Calisthenics can solve 3 control problems that have been discussed in the management control system by previous inventors. Continuing prior research on sports and business relationships that have a very large correlation to improve organizational performance and, comparing the Management Control Systems of Merchant and Stede (2007), Malmi and Brown (1980), most of which fail due to illusion of control. The type of research used is explanatory research (basic research) with qualitative approach method. Where this research is fundamental and aims to obtain information, information, data about things that have not been known related to management control system. The results of the study found differences in the concept of SPM Merchant and Stede (2007), Malmi and Brown (1980) with the SPM concept of Calisthenics that controls employees in the organization by building awareness from within or internal control can be more effective to overcome 3 control issues and overcome the failure Implementation of manajamen control due to illusion of control.